Asymmetric Hydrogenation of Unfunctionalized Tetrasubstituted Acyclic Olefins. Issue 7 (21st January 2020) - Bigler, Raphael; Mack, Kyle A.; Shen, Jeff; Tosatti, Paolo; Han, Chong; Bachmann, Stephan; Zhang, Haiming; Scalone, Michelangelo; Pfaltz, Andreas; Denmark, Scott E.; Hildbrand, Stefan; Gosselin, Francis
Abstract: Asymmetric hydrogenation has evolved as one of the most powerful tools to construct stereocenters. However, the asymmetric hydrogenation of unfunctionalized tetrasubstituted acyclic olefins remains the pinnacle of asymmetric synthesis and an unsolved challenge. We report herein the discovery of an iridium catalyst for the first, generally applicable, highly enantio‐ and diastereoselective hydrogenation of such olefins and the mechanistic insights of the reaction. The power of this chemistry is demonstrated by the successful hydrogenation of a wide variety of electronically and sterically diverse olefins in excellent yield and high enantio‐ and diastereoselectivity. Abstract : Getting a hold of unfunctionalized alkenes : Optimization of the ligand in the iridium catalyst enables the asymmetric hydrogenation (AH) of unfunctionalized tetrasubstituted acyclic olefins, which installs two vicinal stereocenters with excellent stereoselectivies.